Analisis Tingkat Kepuasan Pelanggan Toko Roti Bobo Bakery di Kota Pekanbaru - Jonrio Canway; Fajar Restuhadi; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Bread’s industry have a good prospect in the future. One of many kind bread’s industry that old and eksist until now is bobo bread’s bakery. This business has producted since 1983 located on jalan kuras number 19 Kecamatan Senapelan Kelurahan Kampung Baru in Pekanbaru City. The analysis data use method descriptive quatitative by statistical product service solution (SPSS) version 17. Characteristic security product (permitted, higienis and safety to consume) negative relation and very real with customers address principle security product, it’s more important for customer. Characteristic of customers for income every month it’s real  with fasty attribute service, it’s mean that customers who have in the middle income priority fasty service and characteristic bill out of customers every buy bread it’s very real relation with the kind of taste and the kind of shape, it’s mean customers priority taste because the buy according to their desire. The value of characteristic customers bobo bakery Pekanbaru in this research count 175.54 count by good scale. Key word: Statisfied, Customers, Wish,  Job, Marketing mix, Bobo Bread’s Bakery